Men and the classroom : gender imbalances in teaching - Drudy, Sheelagh (Routledge, Taylor and Francis Group, 2005)
The teaching of young children has long been dominated by women. The authors of this groundbreaking book have undertaken the largest, most in-depth study ever carried out on this topic, in order to assess both teachers and students' views across.